BIODIVERSITY, LOCAL RESOURCE, NATIONAL HERITAGE, REGIONAL CONCERN, AND GLOBAL IMPACT: THE CASE OF MAU FOREST, KENYA - Mutugi, Marion; Kiiru, Winfred (European Scientific Journal, ESJ, 2015)
The Mau Forest situated in western Kenya is is the largest remaining near continuous block of indigenous forest in East Africa. It is a biodiversity haven with a wide range of fauna and flora some of which are endangered. The Mau is important as a water tower feeding rivers and lakes thus supporting livelihoods of millions of people in Kenya and the region. Over the last 20 years an estimated 2000 Km2 of forest was destroyed in the Mau resulting in environmental, social and economic loss. As a major water tower, the impact of this loss is evident lowered water levels in the rivers that emanate from this forest and increased temperatures. In addition are economic losses in agriculture, tourism and energy sectors that affect the livelihoods of people not just in areas adjacent to the Mau but also in neighbouring countires. The unobstructed destruction of the Mau forest continues to deprive the country of a national heritage and is of regional and global concern. Attempts to rehabilitate the Mau have had limited success and they require multidisciplinary local and international support.